MODEL REPRESENTASI INFORMASI DAN PENGETAHUAN UNTUK PROYEK-PROYEK PERUSAHAAN DENGAN MENGGUNAKAN SEMANTIK ONTOLOGI - Azhari Azhari; Subanar Subanar; Retantyo Wardoyo; Sri Hartati (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
This paper presents the utilization of knowledge management system for information and knowledge model development of enterprise projects. This information and knowledge management model is based on ontology semantic data model. The ontology data model is new technique for representing information and knowledge base on more semantically conception of meanings of objects, their properties, and relations between them that may arise within certain domain knowledge. The concern of the knowledge management model is to ensure that the model allows the process of creation, access, and utilization of data in a semantically manner (for querying process) and information or knowledge of enterprise projects. The experimentation shows that project ontology model has satisfied all consistent, valid, complete, and correct ontology model criteria and can be used for semantic reasoning computation. A prototype of the proposed model can access information and knowledge from the knowledge ontology model. Kata Kunci: knowledge management system, semantic data model, ontology model, semantiq query, enterprise projects